2015
DOI: 10.1186/s40200-015-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin as an adjunct therapy to insulin in the treatment of patients with type 1 diabetes mellitus

Abstract: We have evaluated the efficacy of dapagliflozin in patients with type 1 diabetes mellitus (DM1) without adequate control. We expected that adding dapagliflozin to this population on top of their base treatment would lower their HbA1c levels.We conducted a pragmatic, open, 24-week study of treatment with 10 mg of oral dapagliflozin in patients with DM1 and chronic hyperglycemia. We evaluated glycemic control, lipid profile, weight, and insulin dose. Safety was assessed by adverse event reporting.Fasting glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…13,14 In another 24-week study in T1D subjects, dapagliflozin reduced fasting glucose, postprandial glucose, HbA1c, total cholesterol, LDL cholesterol, and triglycerides with no significant adverse events. 15 Similar benefits were seen when dapagliflozin was added to ongoing insulin and liraglutide therapy. 16 Empagliflozin significantly lowered 24-hour UGE in 75 T1D individuals.…”
Section: Clinical Evidence With Sodium-glucose Co-transporter-2 Inhibmentioning
confidence: 84%
See 1 more Smart Citation
“…13,14 In another 24-week study in T1D subjects, dapagliflozin reduced fasting glucose, postprandial glucose, HbA1c, total cholesterol, LDL cholesterol, and triglycerides with no significant adverse events. 15 Similar benefits were seen when dapagliflozin was added to ongoing insulin and liraglutide therapy. 16 Empagliflozin significantly lowered 24-hour UGE in 75 T1D individuals.…”
Section: Clinical Evidence With Sodium-glucose Co-transporter-2 Inhibmentioning
confidence: 84%
“…The prevalence of overweight and obesity among newly diagnosed T1D subjects was 21-22% in the [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] year age group in the Pediatric Diabetes Consortium and the SEARCH for Diabetes in Youth study. 1,2 This has been attributed to a general worldwide increase in prevalence of obesity and similar risk factors such as family history, ethnicity, and sedentary lifestyle may be contributory.…”
mentioning
confidence: 99%
“…The use of these drugs appears to be increasing in young people with T1D despite not being approved 1,[27][28][29][30] . This case illustrates the risk of using these promising drugs when long-term safety studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with Type 2 Diabetes (T2D), Dapagliflozin improves glycosylated hemoglobin (HbA1c) and fasting blood glucose both as monotherapy and in combination with other drugs [3][4][5][6] . Some studies have suggested that SGLT2-I could be useful as an adjuvant to insulin therapy in T1D to improve glycemic control and weight [7][8][9] . However, it has not been approved in children or in T1D.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Use of SGLT2 inhibitors was associated with improvements in average glucose control, reduced postprandial hyperglycemia and glycemic variability, reduced body weight, and reduced insulin dose requirements. [11][12][13] Dual SGLT1/2 inhibitor, sotagliflozin, has also demonstrated significant reductions in HbA1c, postprandial glucose, weight, and insulin doses.…”
Section: Discussionmentioning
confidence: 99%